Heat transfer augmentation of water based TIO2 AND SIO2 nanofluids in a tube with twisted tape - Azmi, W. H. (2015)
Nanofluids have gained extensive attention due to their role in improving the efficiency of thermal systems. Conflicting statements are made in the literature regarding heat transfer enhancements with nanofluids. The objective of the present work is to evaluate heat transfer coefficients through experiments for flow of water, TiO2 and SiO2 nanofluids under similar operating conditions to determine the characteristics under which heat transfer enhancements with nanofluids can be obtained in comparison with water. The properties of TiO2 and SiO2 nanofluids are required at different concentrations, temperature and particle size. Hence, a generalized equation for the evaluation of viscosity and thermal conductivity of nanofluids is developed with the available experimental data in the literature. A test rig is fabricated with the facility to heat the liquid by wrapping with two nichrome heaters on the tube with an option to insert a twisted tape. Experiments are undertaken to determine heat transfer coefficients and friction factor with water based TiO2 and SiO2 nanofluids at 30 oC in the turbulent range of Reynolds number for flow in a tube and with twisted tape. The experimental data indicates enhancement with concentration up to 1 % and 3 % with TiO2 and SiO2 nanofluids respectively for flow in a tube. A maximum of 33 % enhancement at 3 % and 26 % at 1 % volume concentration over water are observed with SiO2 and TiO2 nanofluids respectively for flow in a tube. A further increase in concentration from these values, reduced the heat transfer coefficients. It has been determined that the heat transfer coefficient decrease when the viscosity to thermal conductivity enhancement ratio is greater than 5 which is confirmed with the experimental values of TiO2 and SiO2 nanofluids. It can be stated that enhancement in heat transfer depends on concentration and operating temperature of the nanofluid. An increase in heat transfer coefficient and friction factor with a decrease in twist ratio for water and nanofluids is observed from experiments. The experimental results indicated a maximum heat transfer coefficient of 81.1 % with TiO2 nanofluid at 1 % concentration with insert of twist ratio 5 when compared to flow of water in a tube. However, at the same twist ratio, a maximum enhancement of 94.1 % in heat transfer coefficient at 3 % concentration with SiO2 nanofluid is observed. The nanofluid friction factor with twist ratio of 5 is greater than twice the value obtained for flow of water in a tube at volume concentration higher than 2.5 %. The use of nanofluid is justified from thermo-hydraulic considerations with the estimation of 'advantage ratio'. For the case of plain tubes, it is preferable to have the flow of TiO2 and SiO2 nanofluids at 1 % and 3 % concentrations, respectively. Meanwhile for nanofluid flow with twisted tape, it is recommended to use the twist ratio of 15. The use of TiO2 nanofluids with twisted tape is suggested for volume concentrations higher than 1 %. However, the use of SiO2 nanofluids with twisted tape is not recommended due to lower advantage ratio compared to nanofluid flow in plain tubes. The experimental data of Nusselt number obtained with twisted tape is validated with the results of the theoretical model developed. The characteristics of nanofluid flow and heat transfer are also determined. The flow of nanofluid over a twisted tape is observed to enhance heat transfer.